2024
DOI: 10.1186/s43044-024-00437-x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble guanylate cyclase stimulators for heart failure: a network meta-analysis and subgroup analyses of reduced and preserved ejection fraction

Mohamed T. Abuelazm,
Abdelrahman Attia,
Mohamed Abdelnabi
et al.

Abstract: Background Soluble guanylate cyclase (sGC) stimulators have been investigated for heart failure (HF) in several randomized controlled trials (RCTs). However, its place in the management guidelines of either HFrEF or HfpEF is still inconclusive. Methods We conducted a network meta-analysis synthesizing RCTs investigating sGC for HF management, which were retrieved by systematically searching five databases until January 24th, 2023. Dichotomous outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The largest difference in DBP at 12 weeks was between the placebo and 2.5 mg vericiguat groups (−4.1 mmHg; 95% CI −7.6 to −0.6 mmHg) VITALITY-HFpEF trial [ 125 ]: Among the patients with HFpEF and recent decompensation, 24-week treatment with vericiguat at either 15-mg/day or 10-mg/day dosages compared with placebo did not improve the physical limitation score of the Kansas City Cardiomyopathy Questionnaire LVEF ≥ 45% 92% For all study participants ( N = 789): SBP 129 mmHg, with > 70% above 120 mmHg DBP 73 mmHg Mean changes in SBP at 24 weeks were −3.1 (SD, 14.94) mmHg in the 15-mg/day vericiguat group, −3.8 (SD 4.01) mmHg in the 10-mg/day vericiguat group, and −1.2 (SD 15.42) mmHg in the placebo group. There were no significant changes between the groups in DBP Abuelazm et al 2024 [ 128 ]: Vericiguat 10 mg was effective in reducing the composite CVS mortality and HF hospitalization, with an acceptable safety profile. This was only observed in HFrEF patients, but not in HFpEF patients.…”
Section: Current Drug Therapies For Acute and Chronic Hfpef With Hype...mentioning
confidence: 99%
See 1 more Smart Citation
“…The largest difference in DBP at 12 weeks was between the placebo and 2.5 mg vericiguat groups (−4.1 mmHg; 95% CI −7.6 to −0.6 mmHg) VITALITY-HFpEF trial [ 125 ]: Among the patients with HFpEF and recent decompensation, 24-week treatment with vericiguat at either 15-mg/day or 10-mg/day dosages compared with placebo did not improve the physical limitation score of the Kansas City Cardiomyopathy Questionnaire LVEF ≥ 45% 92% For all study participants ( N = 789): SBP 129 mmHg, with > 70% above 120 mmHg DBP 73 mmHg Mean changes in SBP at 24 weeks were −3.1 (SD, 14.94) mmHg in the 15-mg/day vericiguat group, −3.8 (SD 4.01) mmHg in the 10-mg/day vericiguat group, and −1.2 (SD 15.42) mmHg in the placebo group. There were no significant changes between the groups in DBP Abuelazm et al 2024 [ 128 ]: Vericiguat 10 mg was effective in reducing the composite CVS mortality and HF hospitalization, with an acceptable safety profile. This was only observed in HFrEF patients, but not in HFpEF patients.…”
Section: Current Drug Therapies For Acute and Chronic Hfpef With Hype...mentioning
confidence: 99%
“…Conversely, the VITALITY-HFpEF trial, which investigated the effects of vericiguat treatment over 24 weeks in patients with HFpEF following recent decompensation, did not demonstrate improvement in the KCCQ physical limitation score [ 125 127 ]. A recent network meta-analysis of eight randomized controlled trials with a total of 7307 patients showed that vericiguat did not reduce the composite of cardiovascular mortality and HF hospitalization in patients with HFpEF [ 128 ]. These conflicting findings highlight the need for further research to better understand the role of sGC stimulators in the management of HFpEF and their potential implications for improving patient outcomes.…”
Section: Emerging Drug Therapies For Hfpefmentioning
confidence: 99%